Aqueous rechargeable ammonium ion batteries based on MoS2/MXene with a ball-flower morphology as an anode and NH4V4O10 with a layered structure as a cathode. Issue 15 (23rd March 2023) - Bai, Xue; Yang, Jiahan; Zhang, Fengying; Jiang, Zhuwu; Sun, Fengyi; Pan, Chuntao; Di, Hongcheng; Ru, Shining; Liao, Dongqi; Zhang, Hongyu
Abstract : Assembly of aqueous ammonium ion batteries based on MoS2 /Mxene as an anode and NH4 V4 O10 as a cathode. Abstract : Due to the small hydrated ionic radius and light molar mass of ammonium ions, aqueous ammonium ion batteries attract much attention, providing high security, environmental friendliness and low cost. However, the lack of suitable electrode materials with high specific capacity is a big challenge for practical application. Therefore, in view of this problem, we fabricated an anode applying a MoS2 material with a ball-flower morphology anchored to MXene nanoflakes, and it shows excellent rate capability in a novel aqueous ammonium ion battery. The corresponding charge capacities of composite electrodes are 279.2, 204.4, 173.2, 118.7, and 80.5 mA h g −1 at 20, 50, 100, 200, and 500 mA g −1, respectively. Meanwhile, polyvanadate was selected as a cathode material for a full aqueous ammonium ion battery, and interestingly it was discovered that the size of this material decreases with increasing synthesis temperature. The discharge capacities of NH4 V4 O10 electrodes fabricated at 140 °C, 160 °C, and 180 °C at 50 mA g −1 are 88.6, 125.1 and 155.5 mA h g −1, respectively. Furthermore, we also explore the corresponding electrochemical mechanism using XRD and XPS. A full aqueous ammonium ion battery based on both electrodes shows superior ammonium ion storage properties and provides new ideas for the development of this strategy.